PENGARUH KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT PE PLUS INDONESIA - Aulia Rohalita; Widia Astuti (Jurnal Menara, 2026)
The purpose of this study is to determine how the Influence of Compensation and Work Discipline on Employee Performance at PT PE Plus Indonesia. The method used in this study is a quantitative descriptive method. The sampling technique used is a saturated sampling technique with a sample of 59 respondents. The results of the hypothesis test research obtained a calculated t value > t table or (12.667 > 2.003). Thus, H0 is rejected and Ha is accepted, meaning there is a significant influence between Discipline on Employee Performance. Compensation and Work Discipline have a significant influence on Employee Performance with a linear regression equation Y = 2.172 + 0.412 X1 + 0.532 X2. The correlation coefficient value or the level of relationship between the independent variable and the dependent variable is obtained at 0.807, meaning it has a very strong relationship with the determination coefficient value or simultaneous influence contribution of 0.813 or 81.3% while the remaining 18.7% is influenced by other factors. The hypothesis test obtained F count > F table or (122.097 > 3.16). Thus, H0 is rejected and Ha is accepted. This means that there is a significant simultaneous influence between Compensation and Work Discipline on Employee Performance at PT PE Plus Indonesia.